Induction of flowering in cassava through grafting - Ceballos, Hernán; Jaramillo, J.J.; Salazar Erazo, Sandra Milena; Pineda, Lizzeth Marcela; Calle, Fernando; Setter, Tim L. (Academic Journals, 2017)
Flowering in cassava is related to branching. Erect plant architecture is usually preferred by farmers but results in late and scarce flowering, which slows down breeding and genetic studies. The objective of this study was to induce earlier and more abundant flowering, which have become key research needs for cassava. Six non- or late-flowering genotypes were selected for grafting on a profuse, early flowering understock. Grafted stems did not branch and flower while attached to the understock. Four cuttings from each grafted stem were taken and planted the following season. Paired-row cuttings from non-grafted stems of the same genotypes were planted as checks. Three phenotypic responses to grafting were found. One genotype failed to branch and flower, independently of the origin of the cuttings. Four genotypes branched but did not produce flowers. However, plants from grafted cuttings tended to branch earlier, particularly after the second branching event. Finally, in one genotype, grafting induced not only earlier branching but also earlier and more abundant production of flowers, fruits and seeds than their counterparts of plants from non-grafted stems. This is the first report of grafting effects on the induction of earlier flowering in cassava. Results indicated a delayed effect of grafting which was genotype-dependent based on materials used in this study. The contrasting responses to grafting may be useful for understanding the effect of plant growth regulators and photoperiod manipulations of ongoing research.